2016
DOI: 10.4209/aaqr.2016.01.0008
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Source Apportionment of Atmospheric PM2.5 at a Coastal City in Southern Taiwan

Abstract: Fine particulate matters (PM 2.5 ) has been identified as one of the major air pollutants in urban areas, which are responsible for the adverse effects on public health and the deterioration of visibility. New PM 2.5 air quality standards were promulgated in Taiwan on 14 th May 2012, as well as the standard sampling and analytical method for atmospheric PM 2.5 (NIEA A205.11C) on 24 th April 2012. In this study, the atmospheric levels and characteristics of PM 2.5 in Tainan during 2013 were evaluated by measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…The secondary sulfate (18.2%), secondary nitrate (17.1%), traffic source (15.6%), petrochemical industry (9.08%), resuspending soil particle (8.10%), agricultural open burning (7.79%), sea salt (7.43%), cement industry (5.19%), and metallurgical industry (3.80%) were the main contributing sources in autumn while for winter traffic source (21.6%), secondary nitrate (18.1%), secondary sulfate (13.0%), agricultural open burning (9.89%), petrochemical industry (9.23%), re-suspending soil particle (8.32%), sea salt (5.36%), cement industry (3.20%), and metallurgical industry (3.20%). Similar to our previous study identified ammonium sulfate, ammonium nitrate and traffic sources as the main contributors of PM 2.5 in Tainan City of Taiwan, which indicates that control of PM 2.5 in the ambient air of Chiayi and Tainan Counties should focus on NO x , SO x and traffic emissions (Lu et al, 2016). ), when the lowest one, were registered in the summer (9-22 µg m -3 ) around Chiayi City.…”
Section: Elemental and Organic Carbonsmentioning
confidence: 49%
See 1 more Smart Citation
“…The secondary sulfate (18.2%), secondary nitrate (17.1%), traffic source (15.6%), petrochemical industry (9.08%), resuspending soil particle (8.10%), agricultural open burning (7.79%), sea salt (7.43%), cement industry (5.19%), and metallurgical industry (3.80%) were the main contributing sources in autumn while for winter traffic source (21.6%), secondary nitrate (18.1%), secondary sulfate (13.0%), agricultural open burning (9.89%), petrochemical industry (9.23%), re-suspending soil particle (8.32%), sea salt (5.36%), cement industry (3.20%), and metallurgical industry (3.20%). Similar to our previous study identified ammonium sulfate, ammonium nitrate and traffic sources as the main contributors of PM 2.5 in Tainan City of Taiwan, which indicates that control of PM 2.5 in the ambient air of Chiayi and Tainan Counties should focus on NO x , SO x and traffic emissions (Lu et al, 2016). ), when the lowest one, were registered in the summer (9-22 µg m -3 ) around Chiayi City.…”
Section: Elemental and Organic Carbonsmentioning
confidence: 49%
“…The reason is NO 3 -and NH 4 + will volatilize from surface of PM. Similarly, other studies have shown that NO 3 -, SO 4 2-and NH 4 + as the dominant water soluble ions (Shen et al, 2009;Deshmukh et al, 2011;Wang et al, 2015a;Lu et al, 2016). The higher contribution of NO 3 -and SO 4 2-signifies the occurrence of atmospheric oxidation process for NO 2 and SO 2 (Lin, 2002).…”
Section: Chemical Compositionsmentioning
confidence: 97%
“…Typical sources of air pollution in big cities can be vehicle emissions, dust resuspension, secondary aerosol formation, industrial emissions, biomass or coal burning, power plant emissions etc. (Lu et al, 2016). The characteristics of PM sources have been widely investigated in previous studies all around world, including China, as reviewed by (Karagulian et al, 2015), and several methods of receptor modeling have been used for identification and apportionment of PM (Viana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown good correlations between PM 10 and total-PCDD/Fs mass concentrations (Wang et al, 2010;. Higher PM 2.5 and PCDD/Fs levels are contributed by anthropogenic rather than natural sources, with seasonal variations in these (Yu et al, 2013;Wang et al, 2015;Lu et al, 2016). Ambient particulate matters can be removed from atmosphere by both dry and wet deposition (Cheruiyot et al, 2015(Cheruiyot et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%